An unusual photo‐oxidation pathway for a poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) model compound. Issue 13 (2nd May 2017) - Pickett, James E.
ABSTRACT: The long wavelength UV photochemistry was investigated of a model compound for poly(2, 6‐dimethyl‐1, 4‐phenylene oxide). Irradiation of the phenyl‐capped dimer of 2, 6‐dimethyl phenol at wavelengths >290 nm with UVA‐340 fluorescent lamps in the absence of oxygen gave no detectable products after 27 days. Very low conversion to oxidation products was found in the presence of oxygen, but about 20% conversion to products in which solvent had added to the benzylic methyl groups occurred under aerobic conditions when the solvents had readily abstractable hydrogen atoms. A mechanism is proposed involving the facile, reversible abstraction of a benzylic hydrogen by oxygen as a first step in the oxidation. The hydroperoxyl radical that is formed can abstract hydrogen atoms from 2° and 3° carbons of the solvent, and these radicals can combine with the benzylic radicals to give the solvent adducts. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 2221–2226 Abstract : A model compound for poly(2, 6‐dimethyl‐1, 4‐phenylene oxide) did not exhibit ether bond photolysis when irradiated with UV >290 nm. Rather, it gave products of solvent addition to the methyl groups. This unexpected reaction may proceed from hydrogen abstraction by oxygen from the excited triplet state or from a charge transfer complex.